Cross-linking for microbial keratitis. Issue 4 (July 2016) - Chan, Tommy C.Y.; Agarwal, Tushar; Vajpayee, Rasik B.; Jhanji, Vishal
Abstract : Purpose of review: Microbial keratitis is one of the leading causes of ocular morbidity. The standard treatment consists of antibiotics, which is intensive and is fraught with risks of antibiotic resistance. Corneal collagen cross-linking (CXL) has recently been advocated as an adjunctive therapy for management of microbial keratitis. The addition of CXL to ongoing antimicrobial treatment can have a potential effect on overall duration of the disease, need for corneal transplantation, final visual outcome, and long-term impact on drug resistance pattern. Recent findings: CXL has been used in cases with bacterial, fungal as well as amoebic keratitis. However, so far the reported results have been variable and the evidence is largely anecdotal. The debate over the safety and efficacy of this modality continues especially with regards to its utilization in early phases of the disease when the corneal involvement is limited to the anterior stroma. Summary: CXL appears to be a promising adjunctive treatment in selective cases of mild to moderate bacterial keratitis. Its efficacy in fungal and amoebic keratitis is questionable. Treatment protocols in microbial keratitis need to be individualized. Long-term, prospective, randomized trials are needed to determine its usefulness in microbial keratitis.